A study on the synthesis of gold nanoparticles using water soluble chitosan as reducing/stabilizing agent - Lanh, Le Thi; Hien, Nguyen Quoc; Hoa, Tran Thai; Khieu, Dinh Quang (Vietnam Journal of Chemistry, 2014)
Gold nanoparticles have been synthesized by utilizing water soluble chitosan (WSC) as reducing and stabilizing agent. The colloidal gold nanoparticles were characterized by UV-Vis spectroscopy and transmission electron microscopy (TEM). The results showed that the morphology of gold nanoparticles was spherical in shape with diameters of about 6-17 nm. The colloidal gold nanoparticles were stable and had a plasmon absorption band with maximum wavelength in the range of 520-526 nm. Effects of concentration of Au3+, concentration of water soluble chitosan on the size and plasmon absorption band were also investigated. The size of gold nanoparticles could be enlarged from 14 up to about 35 nm by using seed growth method. Keywords: Gold nanoparticles, synthesis, water soluble chitosan, seed growth.